2022
DOI: 10.3390/brainsci12020159
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunctions in Parkinson’s Disease and Their Influence on Partnership—Data of the PRISM Study

Abstract: Background: Sexual dysfunctions (SD) are common but underreported in Parkinson’s disease (PD) and have negative impacts on the quality of life (QoL) and partnership. Methods: We analyzed the data set from the PRISM study for demographics of SD and their influence on quality of life and partnership. Results: 449/861 (52.1%) PD patients reported SD, with male patients being affected more often and having a longer course of disease. The most common SD in men was erectile dysfunction (ED) (n = 152), while women’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…This suggests that general aspects of short-term SH, extrapolating ED, are influenced by the complex aspects of marital relationship assessment by DAS. Previous studies have shown that the quality of the marital relationship is closely related to SH in both directions [8,34,54]. Our findings reinforce the importance of providing care not only for the patient but also for their partner.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This suggests that general aspects of short-term SH, extrapolating ED, are influenced by the complex aspects of marital relationship assessment by DAS. Previous studies have shown that the quality of the marital relationship is closely related to SH in both directions [8,34,54]. Our findings reinforce the importance of providing care not only for the patient but also for their partner.…”
Section: Discussionsupporting
confidence: 86%
“…Among the social factors, the quality of the marital relationship has been bidirectionally related to SH [34]. Brown et al (1990) showed that couples where one of the partners had PD who reported a better marital relationship were more satisfied with their sex life and vice versa [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a secondary data analysis of a large real-world cross-sectional cohort, Kinateder et al analyzed the prevalence of sexual dysfunction in PD and the impact on the relationship [ 13 ]. Whereas male PD patients most frequently complained of erectile dysfunction, female patients complained in the majority about orgasm dysfunction and reduced libido.…”
mentioning
confidence: 99%
“…Healthcare professionals had no direct role in recruitment and contribution to this study was voluntary, allowing omission to questions that the respondent did not want to answer. Before entering the survey, participants were informed that all information would be treated confidentially and stored securely, in accordance with General Data Protection Regulation 19 …”
Section: Methodsmentioning
confidence: 99%
“…Before entering the survey, participants were informed that all information would be treated confidentially and stored securely, in accordance with General Data Protection Regulation. 19…”
Section: Prism Study Design and Populationmentioning
confidence: 99%